Light at the end of the chip. - Savage, N.
A better photodetector could bring optical data transfer between computer chips closer to reality, according to the IBM researchers who created the device. Such an advance could overcome a looming speed limit-the rate at which data can move between a processor's cores, or from one chip to another, over copper wire.